A Meta-Analysis of Some Determinants of Union Voting Intent - Deshpande, Satish (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1992)
Past literature has identified a need for a detailed investigation of the role of individual characteristics as predictors of individual unionization decision. This research paper uses the Hunter and Schmidt (1990) meta-analytical framework to examine the true impact of specific beliefs about unions, general beliefs about unions, job satisfaction, sex, race, and southern residence on union voting intent. This study also investigates if any of the above relationships are effected by moderator variables.